Blinding in randomized control trials: the enigma unraveled. - Saxena, Vartika; Naithani, Manisha; Mirza, Anissa Atif (Indian Journal of Community Health, 2016)
The search for new treatments and testing of new ideas begins in the laboratory and then established in clinical research settings. Studies addressing the same therapeutic problem may produce conflicting results hence Randomised Clinical Trial is regarded as the most valid method for assessing the benefits and harms of healthcare interventions. The next challenge face by the medical community is the validity of such trials as theses tend to deviate from the truth because of various biases. For the avoidance of the same it has been suggested that the validity or quality of primary trials should be assessed under blind conditions. Thus blinding, is a crucial method for reducing bias in randomized clinical trials. Blinding can be defined as withholding information about the assigned interventions from people involved in the trial who may potentially be prejudiced by this knowledge. In this article we make an effort to define blinding, explain its chronology, hierarchy and discuss methods of blinding, its assessment, its possibility, un-blinding and finally the latest guidelines.